Mathematics
goldwolf
37

Solve by elimination -4x-5y-z=18 -2x-5y-2z=12 -2x+5y+2z=4

+3
(2) Answers
monicabaugh

so -4x-5y-z=18 -2x-5y-2z=12 -2x+5y+2z=4 the 2 last equations look perfect for canceling each other so add them together -2x-5y-2z=12 -2x+5y+2z=4 + -4x+0y+0z=16 -4x=16 divide both sides by 4 -x=4 multiply -1 x=-4 now we have -4x-5y-z=18 -2x+5y+2z=4 add them together -6x+0y+z=22 but x=-4 so -6(-4)+z=22 24+z=22 subtract 24 from both sides z =-2 subsitute into any equation -2x-5y-2z=12 x=-4 z=-2 -2(-4)-5y-2(-2)=12 8-5y+4=12 12-5y=12 subtract 12 from both sides -5y=0 y=0 x=-4 y=0 z=-2

nikolak

-4x - 5y - 1z = 18 ⇒ -4x - 5y - 1z = 18 -2x - 5y - 2z = 12 ⇒ -2x - 5y - 2z = 12 -2x + 5y + 2z = 4    -6x - 10y - 3z = 30                                                                     -6(-4) - 10y - 3z = 30 -4x - 5y - 1z = 18                                             24 - 10y - 3z = 30 -2x - 5y - 2z = 12 ⇒ -2x - 5y -  2z = 12         - 24                  - 24 -2x + 5y + 2z = 4 ⇒ -2x + 5y + 2z = 4                   -10y - 3z = 6                                                 -4x = 16        -10y + 10y - 3z = 6 + 10y                                                  -4     -4                            -3z = 6 + 10y                                                    x = -4                             -3         -3                                                                                             z = -2 - 3¹/₃y                                                                  -10y - 3(-2 - 3¹/₃y) = 6                                                                        -10y + 6 + 10y = 6                                                                        -10y + 10y + 6 = 6                                                                                     0y + 6 = 6                                                                                           - 6 - 6                                                                                            0y = 0                                                                                             0     0                                                                                              y = 0                                                                               -10(0) - 3z = 6                                                                                     -0 - 3z = 6                                                                                      0 - 3z = 6                                                                                    - 0        - 0                                                                                          -3z = 6                                                                                           -3    -3                                                                                             z = -2                                                                                    (x, y, z) = (-4, 0, -2)

Add answer